Inheritance of Benten Dance in Laban Kenagarian Salido Village Subdistrict IV Jurai Pesisir Selatan District - Putri Septia Maharani; Nerosti (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to describe and discuss the Benten Dance Inheritance System in Laban Village, Salido Kanagarian, IV Jurai District, Pesisir Selatan Regency. The type of research used is qualitative with an analytical-descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. The data in this study used primary and secondary data. Data collection techniques are carried out by means of literature study, observation, interviews, and documentation. The steps of analyzing data are data reduction, presenting data, and drawing conclusions. The results showed that the form of inheritance of Benten Dance in Kampung Laban Kanagarian Salido District IV Jurai South Pesisir Regency uses a closed and open inheritance system. The closed inheritance system is carried out by passing on to descendants who have blood relations with the inheritors of Benten dance only. The open inheritance system is carried out by teaching directly to the community either individually or in groups who want to learn benten dance, but must fulfill several predetermined conditions. The weakness of the closed system is that the inheritors of this dance will decrease so that in the long run it could be that this Benten dance will disappear or become extinct. Open inheritance is carried out so that this dance can be preserved in the community and people who learn this Benten Dance really get knowledge and can benefit themselves and others. With the changes that occur in the Benten Dance inheritance system from a closed inheritance system to an open inheritance system, this Benten Dance can still have heirs and can be learned by anyone, both people in Laban Village and people outside Laban Village.